Pengaruh Gaya Hidup, e-WOM, Dan Cashless Society Terhadap Keputusan Dalam Penggunaan Sistem Pembayaran QRIS (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Angkatan 2019 Universitas Islam Malang) - Fina Athiyatur Rohmaniyah; Siti Asiyah; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Changes in the economic field can be felt in that financial activities are carried out more easily and instantly, thereby saving time and effort. The purpose of this study was to determine and analyze the influence of Lifestyle, Cashless Society, and e-WOM simultaneously on the decision to use the Indonesian Standard Quick Response Code payment system. The population in this study were students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2019 who had used QRIS among students of the Islamic University of Malang. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 60 respondents and using the SPSS analysis tool. The results showed that partially Lifestyle and Cashless Society had a significant effect on the decision to use the Quick Response Code Indonesia Standard payment system, while electronic word of mouth had no significant effect on the decision to use the Quick Response Code Indonesia Standard payment system. Simultaneously Lifestyle, Cashless Society, and e-WOM have a significant effect on the decision to use the Quick Response Code Indonesia Standard payment system. Keywords: Lifestyle, Cashless Society, e-WOM, Consumer Decisions